Extracorporeal support for patients with acute and acute on chronic liver failure. (2nd April 2016) - Aron, Jonathan; Agarwal, Banwari; Davenport, Andrew
ABSTRACT: The number of patients developing liver failure; acute on chronic liver failure and acute liver failure continues to increase, along with the demand for donor livers for transplantation. As such there is a clinical need to develop effective extracorporeal devices to support patients with acute liver failure or acute-on-chronic liver failure to allow time for hepatocyte regeneration, and so avoiding the need for liver transplantation, or to bridge the patient to liver transplantation, and also potentially to provide symptomatic relief for patients with cirrhosis not suitable for transplantation. Currently devices can be divided into those designed to remove toxins, including plasma exchange, high permeability dialyzers and adsorption columns or membranes, coupled with replacement of plasma proteins; albumin dialysis systems; and bioartificial devices which may provide some of the biological functions of the liver. In the future we expect combinations of these devices in clinical practice, due to the developments in bioartificial scaffolds.